Huntington’s chorea, a neurological disorder of all ages – Bioinformatics approach for its precise diagnosis: Precise diagnosis of HD using bioinformatics approaches. - Srirama, Krupanidhi; Vineela, J.; Tejaswi, K.; Thanmayi, M.N. (International Journal of Health Sciences, 2019)
Background: The disease that obstructs social movements of people is Huntington’s disease (HD). Hence, the expedition of its molecular aspects and bioinformatics tools relating to precise confirmation of the disease is warranted. Due to social stigma, the care and attention to safeguard these patients had increased at community level. Objective: The objective of the study was to explore bioinformatics tools to trace the defects in Huntington’s gene and design its small-guided RNA (sgRNA). Methodology: The HTT gene sequence was retrieved, CRISPR sites were identified, and gRNA sequence was determined using the University of California Santa Cruz (UCSC) Genome Browser. HTT protein molecular structure elucidation was retrieved through PDB and Swiss Model. Ramachandran plot displayed the cluster of poly-Q at the Phi (−60–−36) and Psi (−60–−65) regions. The pattern of residues in the plot displayed that the HTT protein is alpha-helical predominant. Results: The CRISPR sites on HTT gene are viewed and sgRNA sequences are obtained through the UCSC Genome Browser. This sgRNA sequence along with Cas9 would be planned for genome editing in future experimental models. The Ramachandran plot for HTT protein derived through online Rampage revealed the recurrent appearance of polyglutamine (Q) at the Phi (−55–−65) and Psi (120–135) regions. Conclusion: Online bioinformatic tools such as UCSC Genome Browser, Swiss-Model, and Rampage help in exploring molecular basis of HD and disease-causing protein HTT, and the same invariably assists in creating awareness among health workers.